Does omega-3 supplementation added to exercise attenuate inflammaging? Effects on circulating interleukin-6 in older adults: A meta-analysis of randomized controlled trials - Ni Made Dian Hartaningsih; Desak Made Wihandani; I Made Winarsa Ruma; I Putu Yuda Prabawa (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Low-grade systemic inflammation (inflammaging) characterizes older adults, with circulating interleukin-6 (IL-6) as a key biomarker linked to frailty, physical decline, and cardiometabolic risk. Exercise repeatedly elicits anti-inflammatory myokine responses, while long-chain omega-3 (eicosapentaenoic Acid (EPA)/ docosahexaenoic acid (DHA)) promotes resolution of inflammation via membrane remodelling and specialized pro-resolving mediators. This study aimed to determine whether adding omega-3 supplementation to structured exercise reduces resting IL-6 more than exercise alone in older adults. Methods: A systematic search was undertaken in PubMed using a pre-specified medical subject headings (MeSH) strategy that combined terms for long-chain omega-3 fatty acids, structured exercise/physical activity, Interleukin-6, the aged population, and randomized/clinical trial filters; animal-only studies were excluded. This search yielded 22 records. Complementary searches in Scopus (14 records) and ResearchGate (18 records) were pooled with PubMed results and deduplicated prior to screening. Four RCTs (duration 8–18 weeks) met all criteria. Pooled effects were estimated with a random-effects model using restricted maximum likelihood (REML). Between-study heterogeneity was summarized by Q, I², and τ² summarized between-study heterogeneity. Potential small-study effects were explored visually using a funnel plot. Results: Pooled analysis using a REML model shows that post-intervention IL-6 was lower by 0.77 pg/mL when omega-3 supplementation was added to exercise versus exercise alone (MD = −0.77 pg/mL; 95% CI −1.46 to −0.08; p = 0.03; k = 4), indicating a statistically significant, directionally consistent attenuation of resting inflammation. Between-study heterogeneity was moderate (Q = 7.04, df = 3, p = 0.07; I² = 55%; τ² = 0.26), suggesting that differences in trial characteristics (e.g., duration 8–18 weeks, exercise mode, and omega-3 dose/form) contributed to variability in effect sizes. Funnel-plot analysis did not reveal marked asymmetry. Conclusion: Across randomized trials in older adults, omega-3 supplementation added to exercise achieves a modest but statistically significant reduction in resting IL-6 versus exercise alone, consistent with attenuation of inflammaging.